Effect of Eicosapentaenoic Acid and Docosahexaenoic Acid on Myogenesis and Mitochondrial Biosynthesis during Murine Skeletal Muscle Cell Differentiation - Hsueh, Tun-Yun; Baum, Jamie I.; Huang, Yan (Frontiers in Nutrition, 2018)
Polyunsaturated fatty acids are important nutrients for human health, especially omega-3 fatty acids such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which have been found to play positive roles in the prevention of various diseases. However, previous studies have reported that excessive omega-3 fatty acids supplement during pregnancy caused side effects such as slower neural transmission times and postnatal growth restriction. In this study, we investigated the effect of EPA and DHA on mitochondrial function and gene expression in C2C12 myoblasts during skeletal muscle differentiation. C2C12 myoblasts were cultured to confluency and then treated with differentiation medium that contained fatty acids (50µM EPA and DHA). After 72 hours of myogenic differentiation, mRNA was collected, and gene expression was analyzed by real-time PCR. Microscopy was used to examine cell morphology following treatment with fatty acids. The effect of EPA and DHA on cellular oxygen consumption was measured using a Seahorse XF24 Analyzer. Cells treated with fatty acids had fewer myotubes formed (P ≤ 0.05) compared to control cells. The expression of the genes related to myogenesis was significantly lower (P ≤ 0.05) in cells treated with fatty acids, compared with control cells. Genes associated with adipogenesis had higher (P ≤ 0.05) expression after treatment with fatty acids. Also, the mitochondrial biogenesis decreased with lower (P ≤ 0.05) gene expression and lower (P ≤ 0.05) mtDNA/nDNA ratio in cells treated with fatty acids compared with control cells. However, the expression of genes related to peroxisome biosynthesis was higher (P ≤ 0.05) in cells treated with fatty acids. Moreover, fatty acid treatment reduced (P ≤ 0.05) oxygen consumption rate under oligomycin-inhibited (reflecting proton leak) and uncoupled conditions. Our data imply that fatty acids might reduce myogenesis and increase adipogenesis in myotube formation. Fatty acids may also decrease cell metabolism by reducing mitochondrial biogenesis as well as respiration rate. This study suggests that the maternal overdosage of EPA and DHA may influence fetal muscle development, increase intramuscular adipose tissue deposition in offspring, and have a long-term effect on the development of metabolic diseases such as obesity and diabetes in adult offspring.